Improving the complex surgical treatment of acute purulent cholangitis in gallstone disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Acute purulent cholangitis (APC) is one of the most severe and life-threatening complications of biliary tract diseases, which is an acute inflammation of the bile ducts that occurs against the background of a persistent disturbance in the outflow of bile. The leading cause of impaired bile outflow is cholelithiasis (GSD).